Immunosenescence of Polymorphonuclear Neutrophils - Inga Wessels; Judith Jansen; Lothar Rink; Peter Uciechowski (The Scientific World Journal)
All immune cells are affected by aging, contributing to the high susceptibility to infections and increased mortality observed in the elderly. The effect of aging on cells of the adaptive immune system is well documented. In contrast, knowledge concerning age-related defects of polymorphonuclear neutrophils (PMN) is limited. During the past decade, it has become evident that in addition to their traditional role as phagocytes, neutrophils are able to secrete a wide array of immunomodulating molecules. Their importance is underlined by the finding that genetic defects that lead to neutropenia increase susceptibility to infections. Whereas there is consistence about the constant circulating number of PMN throughout aging, the abilities of tissue infiltration, phagocytosis, and oxidative burst of PMN from aged donors are discussed controversially. Furthermore, there are numerous discrepancies between in vivo and in vitro results, as well as between results for murine and human PMN. Most of the reported functional changes can be explained by defective signaling pathways, but further research is required to get a detailed insight into the underlying molecular mechanisms. This could form the basis for drug development in order to prevent or treat age-related diseases, and thus to unburden the public health systems.